Human Security and the Special Autonomy: The Solution for the Non-traditional Security Issues in Papua? - Setiawan, Hendy; Sa’diyah, Khalimatus (Bestuurskunde: Journal of Governmental Studies, 2022)
Issues of human rights violations, poverty, unemployment, low HDI, low access to education, and poor health are the most important parts of the concept of human security introduced by the UNDP report 1994. These issues have not been adequately addressed in Papua. The purpose of this study was to review the special autonomy arrangements in responding to security issues in Papua. This review was interesting to study because special autonomy has been considered irrelevant to address the human security issues in the province. Human security and special autonomy should be linearly related to each other. As such, the issues of human security should be addressed before the welfare of Papua can be improved. This study used a qualitative approach with a literature study method. The authors collected data through various works of literature in online media, official publications, and others. Meanwhile, the authors followed the Creswell concept to conduct the stages of the study, which consisted of identification of the problem, literature study, determination of study purposes and objectives, collection of data, analysis and interpretation of data, and reporting of the result. The results of the study showed that the implementation of special autonomy and the disbursement of special autonomy funds have been unable to respond to human security issues in Papua. Efforts to improve the welfare of Papua were marred by a conventional security approach. Therefore, these efforts failed to improve the welfare of Papua, triggering ongoing conflicts. Various human security issues in Papua were not addressed properly, such as issues on human rights, public services, health, HDI, economic inequality, and education, which affect its welfare.